A new application of external valvuloplasty using interventional injection of N-butyl cyanoacrylate for malfunctioning venous valves - Hafız, Erhan; Sen, Elzem (Journal of Surgery and Medicine, 2020)
Aim: Chronic venous insufficiency (CVI) is a common disorder that occurs when the venous valves are not working sufficiently. The treatment strategies depend on ameliorating the function of the valves. The aim of this study was to evaluate the external application of N-Butyl Cyanoacrylate to improve venous valves’ functions. Methods: Thirty patients with CVI who were admitted to the cardiovascular surgery clinic with CVI complaints and underwent extravenous N-Butyl Cyanoacrylate application (extravenous application to the area surrounding the malfunctioning venous valves) between January 2020 and June 2020 were included in this retrospective cohort study. Preoperative and postoperative (third and sixth month) venous Doppler ultrasound findings and complaints were noted, and the results were compared. Results: The diameter of the great saphenous vein was found to have decreased during the postoperative period (9.27 (1.95 mm) vs. 6.27 (2.16), P=0.001). Decremental saphenofemoral reflux durations were detected in postoperative ultrasound evaluations when compared with preoperative data (0.77(0.87) vs. 4.77(0.97) seconds). CVI complaints, including oedema, pigmentation and restless leg syndrome, improved within months after the operation. Conclusion: The external application of N-Butyl Cyanoacrylate gel seems effective for recovering venous valve function in the medium term.